Austerity and private debt - Mathias Klein (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This study provides empirical evidence that the costs of austerity crucially depend on the level of private indebtedness. In particular, fiscal consolidations lead to severe contractions when implemented in high private debt states. Contrary, fiscal consolidations have no significant effect on economic activity when private debt is low. These results are robust to alternative definitions of private debt overhang, the composition of fiscal consolidations and controlling for the state of the business cycle and government debt overhang. I show that deterioration in household balance sheets is important to understand private debt-dependent effects of austerity.
Keywords: C23; E32; E62; 330; Fiscal consolidation; Private debt; Local projection